Follow-up of an Asymptomatic Chagas Disease Population of Children after Treatment with Nifurtimox (Lampit) in a Sylvatic Endemic Transmission Area of Colombia - Bianchi, Fiorella; Cucunubá, Zulma; Guhl, Felipe; González, Nadia Lorena; Freilij, Hector; Nicholls, Rubén Santiago; Ramírez, Juan David; Montilla, Marleny; Flórez, Astrid Carolina; Rosas, Fernando; Saavedra, Victor; Silva, Nubia (PLOS Neglected Tropical Diseases, 2015)
Author Summary Chagas disease is currently treated with two drugs, Benznidazole (BNZ) and Nifurtimox (NFX). The need to find the ideal diagnostic technique for post treatment evaluation still exists, due to the known flaws of the currently used techniques. We performed an evaluation of the safety and effectiveness of Nifurtimox treatment in a population of 62 children infected with Trypanosoma cruzi in an endemic Colombian area. The effectiveness was evaluated with two serological tests (IFAT and ELISA), and with two parasitological tests (blood culture and qPCR). We suggest the use of qPCR as a marker of response in all future treatment evaluations for Chagas disease, due to its potential to detect early treatment failure and/or reinfection. In order to have more conclusive results, it is important to perform this kind of study in a controlled environment, wherein the risk of reinfection is not considered.